Economic Vulnerability of Households With Essential Workers - McCormack, Grace (JAMA, 2020)
This study uses 2018 national survey data to characterize the proportion of essential workers in the US overall and living in economically vulnerable households, defined as income <$40 000 or at least 1 member uninsured or older than age 65.